Spontaneous order and the Utopian collective - Nell, Guinevere Liberty; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Spontaneous Order and the Utopian Collective focuses on the Bolshevik theory and early Soviet economic history, delving into the emergence of utopian values and characteristics of recent history.
Keywords: Science